2017
DOI: 10.1021/acs.joc.7b02168
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling Mechanism of a Quinine-Squaramide Catalyzed Enantioselective Aza-Friedel–Crafts Reaction between Cyclic Trifluoromethyl Ketimine and Naphthol: A DFT Study

Abstract: A mechanism study of quinine-squaramide catalyzed enantioselective aza-Friedel-Crafts (aza-F-C) reaction is described using density functional theory (DFT). The most favorable pathway is obtained through the discussions of four possible modes of hydrogen bond interactions, in which the nucleophile is activated by the squaramide N-H groups (N-Ha and N-Hb) and the electrophile binds to the protonated amine by hydrogen bonding. Meanwhile, we have also studied the energy barrier of the stereocontrolling transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…As shown in Figure , on the basis of our experiments and previously reported dual activation model, we proposed a plausible mechanism for this domino Michae/Mannich [3 + 2] cycloaddition reaction. In the first Michael addition step, catalyst C2 initially promotes the formation of transition state A through deprotonation of the N -(2,2,2-trifluoroethyl)­isatin ketimine 2a .…”
Section: Results and Discussionmentioning
confidence: 99%
“…As shown in Figure , on the basis of our experiments and previously reported dual activation model, we proposed a plausible mechanism for this domino Michae/Mannich [3 + 2] cycloaddition reaction. In the first Michael addition step, catalyst C2 initially promotes the formation of transition state A through deprotonation of the N -(2,2,2-trifluoroethyl)­isatin ketimine 2a .…”
Section: Results and Discussionmentioning
confidence: 99%
“…in which the electrophile is activated by the protonated amine group and the deprotonated nucleophile is coordinated to the squaramide [16] . Further proposals have been made and explored involving a „split“ mode of activation wherein either the nucleophile or the electrophile is hydrogen bound to both the protonated amine group and one of the NH‐groups of the squaramide where the other reacting partner is coordinated to the remaining NH‐group of the squaramide (Mode C and D) [17, 18, 19] . When these were explored in the current system, optimizations led to structures assuming either Mode A or B (see Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[16] Further proposals have been made and exploredi nvolving a "split" mode of activation wherein either the nucleophile or the electrophile is hydrogen bound to both the protonated amine group and one of the NH-groups of the squaramide where the other reacting partner is coordinated to the remaining NH-group of the squaramide (Mode Ca nd D). [17,18,19] When these were explored in the current system, optimizations led to structuresa ssuming either Mode Ao rB(see Supporting Information). Furthermore, mono-activated binding modes were explored and were all found to be disfavoured.…”
Section: Resultsmentioning
confidence: 99%
“…Previous computational investigations by Wang and co-workers have indicated that the direct attack of the naphthol additive on the catalyst (quinine-squaramide, in their case) was not favourable. [44] Nevertheless, we have investigated the possibility of proton transfer from the 2-naphthol additive to the quinuclidine nitrogen for the BzCPD catalyst case. The deprotonation of 2naphthol with the concomitant protonation of the quinuclidine nitrogen was seen to be not possible, as the quinuclidine nitrogen gave back the proton to the oxygen of the 2-naphthol (see Figure S3 in SI).…”
Section: Investigation Of the Role Of Phenolic Additives In Different...mentioning
confidence: 99%